The Effectiveness of Uganda's Legal and Policy Framework in Protecting the Right to Health of Refugees - Catherine Neki Nyaketcho (Uganda Christian University, 2025)
Introduction: The purpose of this study is to analyse whether the legal framework and policy of Uganda effectively guarantee and protect the right to health of refugees through the establishment of the elements of the right to health despite the mediating factors. Uganda has been a host to refugees since the aftermath of the First World War. The influx of refugees into the country has surged over time. The Refugee Act, which transformed from the Control of Aliens Act, was established to serve as a principal act governing the affairs of refugees while going about their lives in Uganda. Methods: This research was conducted qualitatively through document analysis. Results: The legal framework of Uganda extends minimal protection to the refugees regarding their right to health, providing mainly for non-discrimination of marginalised groups of women and children. The component of accessibility of medical services or other underlying determinants of health, such as safe water, clean and healthy environment, is hardly established, and as such, the right to health of refugees is ambiguously provided for. With the non-existence of provisions as to accessibility and availability, it is hard to establish the means to attain acceptability and, resultantly, quality of the right to health of the refugees. Conclusion: The legal framework of Uganda, in cognisance of the principal act providing for the affairs of refugees, is effective in protecting the right to health of the refugees to the extent that it covers the components of accessibility guaranteed through protection against discrimination, availability and the underlying determinants of health. The elements of quality and acceptability hang in the balance, as such, the right to health of refugees is offered partial protection by the laws of Uganda. Keywords: The right to health, Refugees, Protection.
Keywords: Right to Health; Protection; Refugees